2013
DOI: 10.1007/s00424-013-1367-0
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-dependent bile salt transporters of the SLC10A transporter family: more than solute transporters

Abstract: Summary The SLC10A transporter gene family consists of seven members and substrates transported by three members (SLC10A1, SLC10A2 and SLC10A6) are Na+-dependent. SLC10A1 (sodium taurocholate cotransporting polypeptide or NTCP) and SLC10A2 (apical sodium-dependent bile salt transporter or ASBT) transport bile salts and play an important role in maintaining enterohepatic circulation of bile salts. Solutes other than bile salts are also transported by NTCP. However, ASBT has not been shown to be a transporter fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
99
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(102 citation statements)
references
References 170 publications
(249 reference statements)
2
99
1
Order By: Relevance
“…These kinases are involved in the regulation of diverse cellular functions (70), including bile formation (35,71). It was suggested that choleretic and cholestatic effects may involve different PKC isoforms; however, the picture is not entirely consistent.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…These kinases are involved in the regulation of diverse cellular functions (70), including bile formation (35,71). It was suggested that choleretic and cholestatic effects may involve different PKC isoforms; however, the picture is not entirely consistent.…”
Section: Discussionmentioning
confidence: 88%
“…Ntcp is a serine/threonine phosphorylated protein (34) and underlies complex regulation (35). cAMP can induce an increase in TC uptake by insertion of Ntcp into the plasma membrane (36) via increases in intracellular Ca 2ϩ and subsequent activation of protein phosphatase 2B (PP2B) via Ca 2ϩ -calmodulin kinase (35). This is associated with a dephosphorylation of Ntcp at Ser-226 (37).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatic FXR activation by (semi-)synthetic FXR agonists has been successful in cholestatic animal models [44,45] in order to induce hepatic bile acid efflux and reduce bile acid uptake and such therapies are now being tested in phase II and III trials in PBC and primary sclerosing cholangitis [46]. In addition to FXR-dependent transcriptional repression of the bile acid uptake machinery, posttranscriptional regulation of the plasma membrane expression and function of NTCP is expected to be relevant during cholestasis, as reviewed elsewhere [47]. So far, the effectiveness of (further) inhibition of basolateral hepatic bile acid uptake in the context of cholestasis was only studied using OATP1A1 knockout mice, which were not protected against hepatic injury after bile-duct ligation [48].…”
Section: Inhibition Of Bile Acid Uptake To Ameliorate Cholestatic LIVmentioning
confidence: 99%
“…Sodium taurocholate cotransporting polypeptide (NTCP), a hepatic membrane transporter for bile acid uptake (6)(7)(8), was recently reported to be an HBV entry receptor (9). The pre-S1 region of the HBV large surface protein (LHBs) interacts with NTCP, which is known to be essential for HBV infection, in mediating the viral entry process (9,10).…”
mentioning
confidence: 99%